2021
DOI: 10.1128/iai.00522-20
|View full text |Cite
|
Sign up to set email alerts
|

Does Antibody Avidity to Plasmodium falciparum Merozoite Antigens Increase with Age in Individuals Living in Malaria-Endemic Areas?

Abstract: Introduction: High avidity antibodies (Abs) are acquired after a few Plasmodium falciparum infections in low transmission areas, but it remains unclear if Ab avidity to different merozoite antigens increases with age in individuals with persistent antigenemia and if so, when a fully mature Ab response occurs. Methods: The study used plasma samples collected between 1996 and 1998 from 566 individuals aged 4-84 years in Simbok, Cameroon where residents received an estimated 1.6 infectious mosquito bites/person/n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The relative IgG avidity against Pfs230 at a time point close to peak malaria season was observed to be significantly higher in older children (≥10 years) than in younger children (<10 years), suggesting that age could have an impact on the avidity. This increase in IgG antibody avidity with the increase in age could be due to increased exposure to the same antigen and hence the tendency of IgG avidity to develop or have matured better in adulthood than in childhood as recently reported ( Tassi Yunga et al., 2021 ). Lack of an association between the number of times a person had been infected with parasites during the follow-ups and antibody levels or avidities was not surprising as all microscopic infections determined contained only asexual parasites.…”
Section: Discussionsupporting
confidence: 59%
“…The relative IgG avidity against Pfs230 at a time point close to peak malaria season was observed to be significantly higher in older children (≥10 years) than in younger children (<10 years), suggesting that age could have an impact on the avidity. This increase in IgG antibody avidity with the increase in age could be due to increased exposure to the same antigen and hence the tendency of IgG avidity to develop or have matured better in adulthood than in childhood as recently reported ( Tassi Yunga et al., 2021 ). Lack of an association between the number of times a person had been infected with parasites during the follow-ups and antibody levels or avidities was not surprising as all microscopic infections determined contained only asexual parasites.…”
Section: Discussionsupporting
confidence: 59%
“…This suggests intrinsic properties of an antigen could impact the avidity of the binding antibody. Previous studies in Ugandan children and adults living in high transmission areas found age-related effects on antibody avidity against some antigens (EBA-175 and MSP1-42) but not others (MSP2 and MSP3) 23 . Studies that have compared malaria antibody avidity between areas of differing transmission have largely focused on blood-stage antigens 22 , 23 .…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies in Ugandan children and adults living in high transmission areas found age-related effects on antibody avidity against some antigens (EBA-175 and MSP1-42) but not others (MSP2 and MSP3) 23 . Studies that have compared malaria antibody avidity between areas of differing transmission have largely focused on blood-stage antigens 22 , 23 . It would be interesting to know if the avidity of antibodies against antigens of pre-erythrocytic and sexual stage show a similar pattern as blood stage antigens.…”
Section: Discussionmentioning
confidence: 82%